(untitled) (LINGUISTICA, 2015)
This study deals with the types of repetition and hesitation in delivering impromptu speech. The objectives of the study were to describe the kinds of repetition and hesitation which used in impromptu speech and why the repetition and hesitation used in delivering impromptu speech. This research applied descriptive quantitative method. The source of data was impromptu speech of English Education class b 2012. Documentary recording as the instrument to collect the data and there were five students to deliver impromptu speech. The data were taken from the utterance of five speechs in impromptu speech into clauses.There were topics prepared for five topics, each speaker varied one another to deliver impromptu speech.The speakers were given 3-5 minutes (maximum) to deliver impromptu speech. Based on the analysis, there were 61 utterances of repetition, the result of the analysis showed that two kinds of repetition; 59.01% of false start and 40.59 % of parentherical remark. And 205 utterances of hesitation, the result of the analysis showed that three kinds of hesitation; 28.78% of filled pause, 43.90% of silent pause and 27.31% of lengthening. The reason why the repetition and hesitation used in impromptu speech because the speakers forgot the words when they were talking or speaker are looking for the right words. Not everyone could speak fluently for all topics of impromptu speech. In general, people were talking, thinking that the hesitation was more difficult than repetition.